Seasonal variation in Proximate composition of Nine Freshwater Fish - Paul, Baidya Nath; Bhowmick, Sadrupa; Singh, Puja; Chanda, Soumen; Sridhar, Narasimhan; Giri, Shiba Shankar (Indian Journal of Animal Nutrition, 2019)
The variation in proximate composition was determined in relation to season and body weight of some freshwater fish i.e. Mystus vittatus, Ompok bimaculatus, Channa striata, Wallago attu and Pangasianodon hypophthalmus, Labeo bata, Labeo calbasu, Cirrhinus reba and Puntius javanicus. The samples were collected at different seasons from different places and were grouped as small (g) and big (g). Nutritional composition of fish species were analyzed during the three seasons i.e. Q1(January-April), Q2(May-August) and Q3 (September-December). Protein content ranged from 12.52-19.19(%) among the species studied on fresh weight basis. Protein content was significantly higher (P<0.01) in C. reba (>100g) during January-April. Protein, fat and ash content of P. javanicus was significantly higher (P<0.01) in fish of size (>100g) during (September-December). Protein content was significantly higher (P<0.05) in O. bimaculatus during Q1 (January-April) irrespective of body size. Protein content was significantly higher (P<0.05) in M. vitattus during Q1 (January-April) irrespective of body weight. Protein content was significantly higher (P<0.01) during the month of May-August in C. striata of size (>500g). Fat content of the L. bata was significantly (P<0.01) higher during Q1 (January to April) irrespective of body size. Fat content in L. calbasu did not differ significantly among seasons. Fat content of C. striata was significantly (P<0.01) higher in size (>100g)during Q1 (January-April). Protein content was significantly higher in W. attu of size(>1000g) during Q2 (May-August). P. hypopthalamus of size (>1000g) revealed that fat content was significantly (P<0.01) higher during Q3 (September-December). Thus it may be concluded that Indian freshwater fishes are enriched with protein, fat and ash and thus qualify as best health food for human consumption.